INVENTARISASI DAN IDENTIFIKASI BAKTERI DAN CENDAWAN PATOGEN PADA TANAMAN PISANG KEPOK (Musa acuminata x Musa balbisiana) DI DESA BAWARANI KABUPATEN NGADA, PROVINSI NUSA TENGGARA TIMUR - Victoria Coo Lea; Nicolaus Noywuli; Umbu Awang Hamakonda; Jenny Ronawati Bay; Victoria Ayu Puspita; Igniosa Taus (Jurnal Agriovet, 2025)
Indications of pest and disease attacks during plant growth cause a decrease in fruit quality. Fungi cause local or systemic symptoms in their host, and these symptoms may occur separately in different hosts, simultaneously in the same host, or one following the other in the same host. Diagnosis and identification of pathogens on a laboratory scale in kepok banana plants in Ngada Regency have not been conducted. Therefore, it is necessary to identify the pathogens causing various disease symptoms in banana plants so that it can serve as preliminary data for further research related to pathogen disease management and information for farmers. This research aims to inventory and identify pathogens causing diseases in banana plants. This research method uses a survey method (purposive sampling) and observation in the plant disease laboratory. The results found several pathogens associated with kepok banana plants, namely Fusarium wilt disease (Fusarium oxysporum and Fusarium graminearum) and bacterial wilt disease (Pseudomonas solanacearum and Ralstonia solanacearum).